Integrating LLM-based agents with uncertainty-aware optimization for water-energy-carbon nexus management in irrigation districts - Lei Yu; Zhikai Li; Kai Huang; Fulin Li; Zixiang Lu; Yurui Fan; Yanan Jiang; Chenglong Zhang; Guangtao Fu (Water Research, 2027)

In-situ catalytic reforming of oily sludge via co-pyrolysis with coal gangue: Pyrolysis kinetics, thermodynamics, and pollutant migration pathways - Chenglong Liu; Li Chao; Bang Yao; Dekai Fan; Yang Liu; Yingwen Zhang; Jianjun Dai (Journal of Environmental Chemical Engineering, 2026)

Internal solitary waves-sloping seabed interaction induced sediment resuspension and seabed multiparameter responses - Cong Hu; Chenglong Zhou; Xiuyao Fan; Chenwei Lu; Chang Su; Tingjie Xu; Mengxue Liu (Advances in Water Resources, 2026)

Dataset Construction of CO2 Flux over Shifting Sand in the Taklimakan Desert and Assessment of Carbon Sequestration Capacity - Ping Yang; Jianping Huang; Fan Yang; Xinqian Zheng; Jiacheng Gao; Meiqi Song; Mingjie Ma; Ali Mamtimin; Chenglong Zhou; Wen Huo; Xinghua Yang; Qingfan Song; et al. (Advances in Atmospheric Sciences, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

Influence of Dynamic Normal Load on Shear Failure Mechanism of Rock Joints: Experimental and Numerical Investigations - Xiaobo Zhang; Le Yi; Chenglong Fan; Yongli Ma; Zhiwei Ye; Chi Yao; Jianhua Yang (Rock Mechanics and Rock Engineering, 2026)

Real-time pneumatic power maximization for oscillating water columns using a spatiotemporally aligned nonlinear model predictive control - Yan Huang; Xiaofu Ma; Weiwei Fan; Yongqiang Tu; Shaohui Yang; Jianyu Fan; Chenglong Li; Zhichang Du; Yuankui Wang (Ocean Engineering, 2026)

Geodynamic controls on the habitable basement of shallow coral reefs at rifted continental margins - Zhibin Lei; Shaohong Xia; Sascha Brune; Michaël Pons; Chenglong Zhang; Tao Gou; Changrong Zhang; Chaoyan Fan (Earth and Planetary Science Letters, 2026)

Embodied artificial intelligence in the food supply chain: Innovations, challenges, and future perspectives - Chongyu Wang; Chenglong Lv; Yixin Gao; Yiyang He; Xiyao Zhang; Zhikun Zhang; Weiqing Min; Dachuan Zhang; Daming Fan; Weihao Wang; Peihua Ma; Fengzhong Wang (Trends in Food Science & Technology, 2026)

Nonlinear drivers of canopy and surface urban heat islands across China’s climate zones: marginal and interaction effects from explainable machine learning - Cong Wen; Ali Mamtimin; Haitao Wang; Yu Wang; Haotong Liu; Hajigul Sayit; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Yisilamu Wulayin; Fan Yang; Chenglong Zhou; et al. (Sustainable Cities and Society, 2026)

A predictive efficiency maximization method based on active airflow control for an oscillating water column turbine - Yan Huang; Xiaofu Ma; Weixun Dong; Yongqiang Tu; Shaohui Yang; Jianyu Fan; Chenglong Li; Zhichang Du; Yuankui Wang (Ocean Engineering, 2026)

Study on vibration reduction performance of stay cable self-centering composite jacket offshore wind turbine - Chenglong Shi; Jigang Zhang; Wenli Chen; Qinglai Fan; Ruyang Shi; Jin Miao (Ocean Engineering, 2026)

Observed and modeled interactions between atmospheric pollutants and urban thermal environment in an arid city: Urumqi as a case study - Cong Wen; Yu Wang; Ali Mamtimin; Jian Peng; Hajigul Sayit; Jiali Feng; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Junjian Liu; Yisilamu Wulayin; Chenglong Zhou; et al. (Atmospheric Environment, 2026)

Three-dimensional dust distribution and transport over the northern hemisphere dust belt: Insights from lidar observations - Ruiqi Tan; Tianhe Wang; Ying Han; Jingtao Li; Jingyi Tang; Sichen Wang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Bakhriddin E. Nishonov; Mansur O. Amonov; Sabur F. Abdullaev (Atmospheric Research, 2026)

Divergent driving mechanisms elevate antibiotic resistance risk to a greater extent in water than in sediment of the Ganjiang River: The synergistic effect of mobile genetic elements and microbial metabolism - Dingchang Li; Rongmei Zhu; Xiaoyan Fan; Huihui Dai; Chenglong Zou; Yanling Wang; Jinchi Yao; Huimin Zhang; Chuqiao Wang; Shan Huang (Journal of Environmental Chemical Engineering, 2026)

Real-time magnitude estimation of large earthquakes utilizing combined strong motion and GPS data - Dingwen Zhang; Xiaoran Fan; Qibo Hu; Chenglong Li; Xinjian Shan; Guohong Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Magnetic activated biochar prepared via a novel iron-loading method for efficient lead adsorption and recyclability - Li Chao; Bang Yao; Chenglong Liu; Yang Liu; Chunbao Zhou; Yingwen Zhang; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Jing Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Quantifying freeze-thaw erosion dynamics in retrogressive thaw slumps: integrating geophysical and experimental approaches - Chenglong Jiao; Fujun Niu; Jing Luo; Peifeng He; Fan Yu (CATENA, 2025)

Proteomic Signatures of Dental Enamel Hypomineralization: Divergent Molecular Pathways in Coal-Burning vs. Drinking-Water Fluorosis - Na Yang; Jiabing Fan; Guobao Man; Wentai Wang; Jian Liao; Chenglong Tu (Biological Trace Element Research, 2025)

Dust emission contributions and regulatory mechanisms of dust devils in the Taklimakan Desert - Mingjie Ma; Xinghua Yang; Fan Yang; Qing He; Ali Mamtimin; Xiannian Zheng; Chenglong Zhou; Wen Huo (Natural Hazards, 2025)

Plant and microbial-mediated soil organic carbon accumulation and stabilization in an estuary salt marsh wetland: Implications for blue carbon formation - Qihang Liao; Zhuoyue Zhang; Feng Yuan; Yue Xue; Meicai Xu; Qinya Fan; Ming Lu; Xiao Huang; Penghua Qiu; Chenglong Wang; Xinqing Zou (Applied Soil Ecology, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

In situ catalytic pyrolysis of oily sludge using coal gangue char to produce naphthalene-rich oil and hydrogen-rich gas - Chenglong Liu; Yunxiang Li; Dekai Fan; Pengfei Zhu; Yang Liu; Li Chao; Chunbao Zhou; Bang Yao; Yingwen Zhang; Jianjun Dai (Chemical Engineering Journal, 2025)

Maturity recognition and localisation of broccoli under occlusion based on RGB-D instance segmentation network - Shuo Kang; Jiali Fan; Yongkai Ye; Chenglong Li; Dongdong Du; Jun Wang (Biosystems Engineering, 2025)

Pyrogenic carbon records of Holocene fire dynamics in the Yellow River Basin: Climate change and human activity forcing - Chuchu Zhang; Yifei Qiu; Chenglong Wang; Qinya Fan; Ziyue Feng; Xinqing Zou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessment of CO2 fluxes in the hinterland of the Gurbantunggut Desert and its response to climate change - Ali Mamtimin; Gulnur Amar; Yu Wang; Jian Peng; Hajigul Sayit; Jiacheng Gao; Kun Zhang; Meiqi Song; Ailiyaer Aihaiti; Cong Wen; Fan Yang; Wen Huo; et al. (Journal of Environmental Management, 2025)

Enhanced bio-immobilization of perrhenate by driving microbial extracellular electron transfer: Evidence from spectroscopy and DFT calculations - Haoqing Zhang; Bo Li; Tianwei Qian; Xiaona Liu; Fan Li; Yixuan Gao; Jianhui Wang; Lei Zhang; Chenglong Xu (Chemical Engineering Journal, 2025)

Interactions between dust aerosols and the ultra-high atmospheric boundary layer: Case study of vertical observation over the Taklimakan Desert, China - Lu Meng; Qing He; Tianliang Zhao; Hongsheng Zhang; Xinghua Yang; Ali Mamtimin; Fan Yang; Chenglong Zhou; Wen Huo (Atmospheric Environment, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

Association of spring thermal forcing anomalies in the Tibetan Plateau with dust aerosol changes over the Taklamakan Desert - Lu Meng; Qing He; Tianliang Zhao; Zhimin Yi; Rehana Khan; Ali Mamtimin; Fan Yang; Chenglong Zhou; Xinghua Yang; Wen Huo (Science of The Total Environment, 2025)

Daytime radiative freezing - Yi Zhang; Chenglong She; Jingjing Chen; Kui Lai; Keqiao Li; Fan Yang; Chenxi Wang; Baoling Huang; Lihua Shen; Xiaobo Yin (Science Bulletin, 2025)

Solar-driven hydrogen and water co-generation based on atmospheric water harvesting - Chenglong Qin; Tingting Ren; Chengxiang Gui; Peng Liu; Qingjiao Wei; Wenjing Liu; Zuwei Zhou; Yaning Huang; Kun Fan; Lu Huang (Chemical Engineering Journal, 2025)

Synergistic interaction of char-volatile/volatile-volatile on PAHs formation during waste printed circuit boards pyrolysis: Evolution pathway and mechanisms - Yingwen Zhang; Chunbao Zhou; Yang Liu; Bang Yao; Li Chao; Dekai Fan; Mengyan Yu; Chenglong Liu; Jianjun Dai (Chemical Engineering Journal, 2025)

Grazing weakens the carbon sequestration capacity of dry temperate grassland ecosystems in Central Asia - Yuangang Wang; Geping Luo; Chaofan Li; Yu Zhang; Chenglong Zhang; Xiaotong Yu; Binbin Fan; Wenqiang Zhang; Mingjuan Xie; Yujia Liu (CATENA, 2025)

Study on association between human plasma polybrominated diphenyl ethers (PBDEs) and thyroid homeostasis and carcinoma - Qianqian Wang; Yi Wang; Chunyan Chen; Likun Zhang; Chenglong Wang; Xinyu Lou; Dan Chen; Jun Jin; Youben Fan; Shaofeng Sui; Zhiyan Liu (Environmental Geochemistry and Health, 2024)

Precipitation Controls on Carbon Sinks in an Artificial Green Space in the Taklimakan Desert - Yingwei Sun; Fan Yang; Jianping Huang; Xinqian Zheng; Ali Mamtimin; Chenglong Zhou; Silalan Abudukade; Jiacheng Gao; Chaofan Li; Mingjie Ma; Wen Huo; Xinghua Yang (Advances in Atmospheric Sciences, 2024)

Production of aromatic-rich oil from marine oily sludge via in situ catalytic pyrolysis using coal gangue - Chenglong Liu; Dekai Fan; Yang Liu; Chunbao Zhou; Li Chao; Bang Yao; Yingwen Zhang; Jianjun Dai; Lei Chen; Jie Dong; Jun Wang; Xuyang Xing; et al. (Fuel, 2024)

N-octyltrimethylammonium bromide-assisted self-assembly of CoMo precursors to prepare CoMoS/Al2O3 catalysts for highly selective hydrodesulfurization of thiophene - Shuisen He; Xueman Wang; Chenglong Wen; Yu Fan (Fuel, 2024)

RotatedStomataNet: a deep rotated object detection network for directional stomata phenotype analysis - Xiaohui Yang; Jiahui Wang; Fan Li; Chenglong Zhou; Minghui Wu; Chen Zheng; Lijun Yang; Zhi Li; Yong Li; Siyi Guo; Chunpeng Song (Plant Cell Reports, 2024)

Process and systematic study of gold recovery from flexible printed circuit boards (FPCBs) using a choline chloride–ethylene glycol system - Ruixue Wang; Guoliang Fan; Chenglong Zhang (Waste Management, 2024)

Structural characterization of steranes and hopanes in petroleum by ion mobility mass spectrometry - Chenglong Dong; Jing Xie; Zhaoyang Fan; Yinghao Wang; Jikun Liu; Haodong Wang; Guangyou Zhu; Yehua Han (Fuel, 2024)

Microplastics: A potential proxy for tracing extreme flood events in estuarine environments - Hongyu Chen; Yu Cheng; Ying Wang; Yongcheng Ding; Chenglong Wang; Xuguang Feng; Qinya Fan; Feng Yuan; Guanghe Fu; Bingfei Gao; Kai Liu; Xinqing Zou (Science of The Total Environment, 2024)

Tumoral/exosomal PD-L1 silencing reinforces mild photothermal therapy by relieving systemic and local immunosuppression - Huan Ye; Jing Yan; Chenglong Ge; Fan Wu; Junliang Zhu; Mengyuan Yin; Lucheng Xie; Zhuchao Zhou; Lichen Yin (Chemical Engineering Journal, 2024)

Plant- and microbial-mediated soil organic carbon accumulation in Spartina alterniflora salt marshes - Qihang Liao; Feng Yuan; Qinya Fan; Hongyu Chen; Yameng Wang; Chuchu Zhang; Chao Lu; Penghua Qiu; Chenglong Wang; Xinqing Zou (CATENA, 2024)

Terrain effects of the Tibetan Plateau on dust aerosol distribution over the Tarim Basin, China - Chenglong Zhou; Xinghua Yang; Yuzhi Liu; Qingzhe Zhu; Yongkun Xie; Fan Yang; Mamtimn Ali; Wen Huo; Qing He; Lu Meng (Atmospheric Research, 2024)

Molecular phylogeny, historical biogeography, and classification of Pseudocoladenia butterflies (Lepidoptera: Hesperiidae) - Yongxiang Hou; Chenglong Cao; Hideyuki Chiba; Zhou Chang; Siyao Huang; Lijuan Zhu; Krushnamegh Kunte; Zhenfu Huang; Min Wang; Xiaoling Fan (Molecular Phylogenetics and Evolution, 2023)

Soil carbon-fixing bacterial communities respond to plant community change in coastal salt marsh wetlands - Qihang Liao; Chao Lu; Feng Yuan; Qinya Fan; Hongyu Chen; Lin Yang; Penghua Qiu; Ziyue Feng; Chenglong Wang; Xinqing Zou (Applied Soil Ecology, 2023)

Submarine volcanism in the southern margin of the South China Sea - Chenglong Zhang; Shaohong Xia; Chaoyan Fan; Jinghe Cao (Journal of Oceanology and Limnology, 2023)

SBA-15-supported ultrastable Mo2N@CN catalysts for hydrodeoxygenation of guaiacol - Fan Wang; Chenglong Wen; Mohong Lu; Peng Zhang; Jie Zhu; Mingshi Li; Yuhua Shan; Chunshan Song (Biomass and Bioenergy, 2023)

Changes in distribution and morphology of Tamarix ramosissima nebkhas in an oasis-desert ecotone - Chaofan Li; Fan Yang; Xinqian Zheng; Zhangyong Han; Honglin Pan; Chenglong Zhou; Chunrong Ji (Geosciences Journal, 2021)

Comparison and Analysis of Meteorological Variables Observed from the Glacier Area over the Tianshan Mountains in Kyrgyzstan and China - Honglin Pan; Wen Huo; Kanike Raghavendra Kumar; Ali Mamtimin; Minzhong Wang; Junjian Liu; Chenglong Zhou; Fan Yang; Xinghua Yang (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Evaluation of wind erosion in the Tarim Basin based on parameter localization - Chenglong Zhou; Fan Yang; Wen Huo; Honglin Pan; Lu Meng; Ali Mamtimin; Huoqing Li; Xinghua Yang (Theoretical and Applied Climatology, 2020)

Influence of Configuration on Stress Distribution of Pulmonary Monocusp Leaflet - Wentao Feng; Yishan Teng; Jie Yao; Xianda Yang; Chenglong Feng; Yubo Fan (Cardiovascular Engineering and Technology, 2020)

Relationship between air temperature and horizontal sand-dust flux observed in the Taklimakan Desert, China - Chenglong Zhou; Ali Mamtimin; Honglin Pan; Fan Yang; Wen Huo; Lu Meng; Lili Jin; Xinghua Yang (Theoretical and Applied Climatology, 2019)

Dust uplift potential in the Taklimakan Desert: an analysis based on different wind speed measurement intervals - Chenglong Zhou; Ali Mamtimin; Fan Yang; Wen Huo; Minzhong Wang; Honglin Pan; Qing He; Lili Jin; Xinghua Yang (Theoretical and Applied Climatology, 2019)

A study on the effects of soil moisture, air humidity, and air temperature on wind speed threshold for dust emissions in the Taklimakan Desert - Xinghua Yang; Chenglong Zhou; Wen Huo; Fan Yang; Xinchun Liu; Ali Mamtimin (Natural Hazards, 2019)

An inexact irrigation water allocation optimization model under future climate change - Youzhi Wang; Liu Liu; Ping Guo; Chenglong Zhang; Fan Zhang; Shanshan Guo (Stochastic Environmental Research and Risk Assessment, 2019)

Comparison of approaches for calculating the threshold velocity for sand movement based on field experiments in Xinjiang, China - Chenglong Zhou; Qing He; Wen Huo; Fan Yang; Ali Mamtimin; Pan Honglin; Xinghua Yang (Arabian Journal of Geosciences, 2018)

Isolation and characterization of a C-repeat binding factor (CBF)-like gene in cassava (Manihot esculenta Crantz) - Ruimei Li; Yimeng Ji; Jie Fan; Chenglong Yang; Yuan Yao; Yang Zhou; Ruijun Duan; Jiao Liu; Shaoping Fu; Xinwen Hu; Jianchun Guo (Acta Physiologiae Plantarum, 2014)

Biomechanism of impact resistance in the woodpecker’s head and its application - LiZhen Wang; Shan Lu; XiaoYu Liu; XuFeng Niu; Chao Wang; YiKun Ni; MeiYa Zhao; ChengLong Feng; Ming Zhang; YuBo Fan (Science China Life Sciences, 2013)